TO EVALUATE EFFICACY AND SAFETY OF RUPATADINE, BILASTINE, AND LEVOCETRIZINE IN ALLERGIC RHINITIS AT TERITARY CARE HOSPITAL, TELANGANA - GRACE, NAGUR SHARONE; AHMED, SYED ARSHADDUDDIN; E, BHUVANESWARI; QUADRI, SYED HAMZA; B, VEENA; N, MONICA; KUMAR, VALISHETTI MANOJ (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Allergic rhinitis (AR) is a heterogeneous disorder characterized by symptoms – sneezing, itching, nasal congestion, and rhinorrhea. The aim of the study is to evaluate the efficacy and safety of rupatadine, bilastine, and levocetirizine in AR. Methods: A prospective, open-label, comparative study was conducted at the Government ENT Hospital, Hyderabad, Telangana. Ninety patients diagnosed with AR were randomized, of whom Group 1 received oral tab. bilastine 20 mg once daily, Group 2 received oral tab. levocetirizine 5 mg once daily, and Group 3 received oral tab. rupatadine with a dose of 10 mg once daily for 2 weeks. The reduction in total nasal symptom score (TNSS) and absolute eosinophil counts (AECs) was compared with baseline and at 2 weeks. Safety was assessed according to adverse events reported during the study period. An analysis of variance was used as a test of significance for the three groups. Results: Overall, 90 cases were included in the study, with 48% of males and 52% of females. All three drugs significantly reduced the TNSS and AEC after treatment compared to before treatment (p<0.05). The mean difference in TNSS and AEC showed no statistically significant difference among the three groups (TNSS: p>0.908 and AEC: p>0.967). In terms of safety, all three drugs showed nearly similar adverse events. Conclusion: In this study, after 2 weeks of follow-up, the three drugs (bilastine, levocetirizine, and rupatadine) showed significant improvement clinically, but the mean reduction in the score of symptoms and AEC was not statistically significant in the treatment of AR.